2007
DOI: 10.1002/ejic.200700314
|View full text |Cite
|
Sign up to set email alerts
|

Structurally Characterized Erbium Alkoxides for Use as an Amphoteric Dopant in PErZT Ceramic Thin Film and Nanoparticles

Abstract: A family of erbium alkoxides [Er(OR)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 40 publications
(75 reference statements)
2
23
0
Order By: Relevance
“…Light green, moisture- and air-sensitive crystals grown from a concentrated solution in toluene at 4 °C revealed a trigonal arrangement of praseodymium atoms (Figure ) supported by three doubly bridging alkoxy ligands present along the sides of the hypothetical triangle (O3, O4, and O5). Two additional μ 3 -bridging alkoxy ligands (O1 and O2) are present below and above the triangular plane, resulting in a 6-fold oxygen coordination around each of the Pr centers as generally favored by this class of lanthanide compounds. , The obtained molecular structure is similar to those reported for yttrium, lanthanum, terbium, and gadolinium tert -butoxides. ,,, Herein, the Pr–O bond lengths (Table ) fit well with the trend of the Ln–O bond lengths within the lanthanide series, exhibiting shorter bond lengths with increasing atomic number (selected bond lengths between Ln and μ 3 -bridging O: La, 2.505 (13) Å; Pr, 2.4721(17) Å; Nd, 2.409 (13) Å; Gd, 2.3610 (15) Å; Tb, 2.343(3) Å; Er, 2.305(3) Å) (selected bond lengths between Ln and μ 2 -bridging O: La, 2.449(14) Å; Pr, 2.4137(18) Å; Nd, 2.399(3) Å; Gd, 2.3313(16) Å; Tb, 2.320(4) Å; Er, 2.269(3) Å) (selected bond lengths between Ln and terminal alkoxy as well as tert -butyl alcohol (with the exception of the Nd complex where THF was reported as a molecule ligate) ligands: La, 2.195(13) Å/2.604(15) Å; Pr, 2.1912(18) Å/2.6639(19) Å; Nd, 2.147(4) Å/2.661(4) Å; Gd, 2.1223(16) Å/2.5567(16) Å; Tb, 2.114(4) Å/2.609(4) Å; Er, 2.067(3) Å/2.525(4) Å). Despite its discrete molecular structure, 1 cannot be vaporized due to coordinated alcohol ligands that are removed under vacuum, thus producing higher agglomerates with evidently low vapor pressure.…”
Section: Resultssupporting
confidence: 75%
“…Light green, moisture- and air-sensitive crystals grown from a concentrated solution in toluene at 4 °C revealed a trigonal arrangement of praseodymium atoms (Figure ) supported by three doubly bridging alkoxy ligands present along the sides of the hypothetical triangle (O3, O4, and O5). Two additional μ 3 -bridging alkoxy ligands (O1 and O2) are present below and above the triangular plane, resulting in a 6-fold oxygen coordination around each of the Pr centers as generally favored by this class of lanthanide compounds. , The obtained molecular structure is similar to those reported for yttrium, lanthanum, terbium, and gadolinium tert -butoxides. ,,, Herein, the Pr–O bond lengths (Table ) fit well with the trend of the Ln–O bond lengths within the lanthanide series, exhibiting shorter bond lengths with increasing atomic number (selected bond lengths between Ln and μ 3 -bridging O: La, 2.505 (13) Å; Pr, 2.4721(17) Å; Nd, 2.409 (13) Å; Gd, 2.3610 (15) Å; Tb, 2.343(3) Å; Er, 2.305(3) Å) (selected bond lengths between Ln and μ 2 -bridging O: La, 2.449(14) Å; Pr, 2.4137(18) Å; Nd, 2.399(3) Å; Gd, 2.3313(16) Å; Tb, 2.320(4) Å; Er, 2.269(3) Å) (selected bond lengths between Ln and terminal alkoxy as well as tert -butyl alcohol (with the exception of the Nd complex where THF was reported as a molecule ligate) ligands: La, 2.195(13) Å/2.604(15) Å; Pr, 2.1912(18) Å/2.6639(19) Å; Nd, 2.147(4) Å/2.661(4) Å; Gd, 2.1223(16) Å/2.5567(16) Å; Tb, 2.114(4) Å/2.609(4) Å; Er, 2.067(3) Å/2.525(4) Å). Despite its discrete molecular structure, 1 cannot be vaporized due to coordinated alcohol ligands that are removed under vacuum, thus producing higher agglomerates with evidently low vapor pressure.…”
Section: Resultssupporting
confidence: 75%
“…Formation of a crystalline Pr III tert ‐butoxide was described by Hubert‐Pfalzgraf et al; however, no crystallographic data on the molecular structure was reported 2. We have recently characterized the praseodymium and gadolinium tert ‐butoxides,3 which were found to be analogous to the yttrium,4 lanthanum,1 cerium,5 erbium6 and dysprosium7 compounds.…”
Section: Introductionmentioning
confidence: 93%
“…Tris(triphenylsiloxide) complexes of Ln( iii ) were extensively studied after being first reported 30 years ago, 7–10 and the structure of several [M III (OSiPh 3 ) 3 (THF) 3 ] complexes (M = La, 7 b Ce, 8 Sm, 9 Dy, 10 and Er 11 ) is known. The triphenylsiloxide ligand was also reported to stabilize the Ce( iv ) complex [Ce(OSiPh 3 ) 4 (DME)] 12 more than thirty years ago but no attempts were made until recently 4,5 c to use the same ligand for stabilizing other Ln( iv ) ions.…”
Section: Introductionmentioning
confidence: 99%